2005
DOI: 10.1002/cncr.21469
|View full text |Cite
|
Sign up to set email alerts
|

A metaanalysis of studies of the effects of cancer chemotherapy on various domains of cognitive function

Abstract: BACKGROUNDLittle is known about the effects of chemotherapy on cognitive function. The purposes of this metaanalysis were to estimate the effect sizes for the effect of chemotherapy on each domain of cognitive function and to differentiate effect sizes by each method of comparison of effects (i.e., normative data, control group, or baseline data).METHODSSixteen studies that evaluated cognitive function in chemotherapy patients were included in the study. DSTAT metaanalysis software was used to calculate an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
117
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(127 citation statements)
references
References 60 publications
5
117
0
5
Order By: Relevance
“…The results were mixed: Poorer performances were reported among patients who received chemotherapy, 2,3,5,7 although others reported no differences 16,17 ; the latter findings also were supported by a meta-analysis. 21 Two longitudinal studies that provided evidence of chemotherapy effects on cognitive function were limited by their rather small sample sizes (Wefel et 18 did not identify any significant differences in cognitive changes between chemotherapy patients, nonchemotherapy patients, and healthy control individuals. The patients were heterogeneous with regard to the chemotherapy regimens administered, with most patients having received only relatively low-dose combined 5-fluorouracil, epirubicin, and cyclophosphamide treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were mixed: Poorer performances were reported among patients who received chemotherapy, 2,3,5,7 although others reported no differences 16,17 ; the latter findings also were supported by a meta-analysis. 21 Two longitudinal studies that provided evidence of chemotherapy effects on cognitive function were limited by their rather small sample sizes (Wefel et 18 did not identify any significant differences in cognitive changes between chemotherapy patients, nonchemotherapy patients, and healthy control individuals. The patients were heterogeneous with regard to the chemotherapy regimens administered, with most patients having received only relatively low-dose combined 5-fluorouracil, epirubicin, and cyclophosphamide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Meta-analyses also consistently have stated that it depends on the study design whether chemotherapy-related cognitive impairment is observed, with more appropriate designs resulting in less clear evidence or no evidence of chemotherapy-induced cognitive impairment. [19][20][21] Currently, we are conducting a multicenter, prospective study entitled Cognitive Impairment in Therapy of Breast Cancer (COGITO). Cognitive function in early breast cancer patients is assessed before the start of neoadjuvant chemotherapy, toward the end of chemotherapy, and 1 year after the baseline assessment.…”
mentioning
confidence: 99%
“…These declines in cognitive performance are subtle, with the most commonly affected domains being verbal memory, language, visual memory/ spatial ability and executive functioning (for meta-analyses, see Faletti, Sanfi lippo, Maruff, Weih, & Phillips, 2005 ;Jansen, Miaskowski, Dodd, Dowling, & Kramer, 2005 ;Stewart, Bielajew, Collins, Parkinson, & Tomiak, 2006 ). However, reports of affected domains are variable, with some studies fi nding global diffi culties (e.g., Schagen et al, 1999 ;Scherwath et al, 2006 ;Wieneke & Dienst, 1995 ) and some fi nding K.J.…”
Section: Introductionmentioning
confidence: 99%
“…3,13,14 Contradictory results exist concerning the extent of impairments either before, or after chemotherapy. Finding deviations from norms before treatment leads to the discussion of other factors not directly associated with the treatment such as influence of the malignancies themselves or psychological factors (anxiety, treatment-related distress, depression).…”
Section: Introductionmentioning
confidence: 99%